2015
DOI: 10.1002/uog.15069
|View full text |Cite
|
Sign up to set email alerts
|

OC19.04: Sonography of responsive versus non‐responsive ectopic pregnancies

Abstract: Objectives: To assess if Doppler ultrasound improves the diagnostic accuracy of histologically confirmed RPOC. Examination of inter observer variability in diagnosis and measurement of RPOC. Methods: Retrospective analysis of and image review from ultrasound database of diagnoses of incomplete miscarriage in a tertiary referral early pregnancy unit from January to December 2014. Histological concordance was sought for those undergoing surgical management. Scan images were reviewed by two independent sonographe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…First observations of the evolution of EP vascularity following MTX therapy showed that in the majority of cases successfully managed with MTX therapy, an initial increase in the vascularity of the ectopic mass is observed and should not prompt concern (15) . Another study, however, demonstrated that increasing vascularity linked to a growing β-hCG level is found in cases unresponsive to MTX therapy, whereas in responsive cases the vascularity is seldom observed (17) . Thus, the significance of the changes in EP vascularity following MTX therapy has yet to be determined, with the most recent data pointing to the conclusion that a rise in the vascularity may be indicative of treatment failure.…”
Section: Evolution Of the Vascularity Of The Ectopic Mass Following Mtx Therapymentioning
confidence: 96%
See 1 more Smart Citation
“…First observations of the evolution of EP vascularity following MTX therapy showed that in the majority of cases successfully managed with MTX therapy, an initial increase in the vascularity of the ectopic mass is observed and should not prompt concern (15) . Another study, however, demonstrated that increasing vascularity linked to a growing β-hCG level is found in cases unresponsive to MTX therapy, whereas in responsive cases the vascularity is seldom observed (17) . Thus, the significance of the changes in EP vascularity following MTX therapy has yet to be determined, with the most recent data pointing to the conclusion that a rise in the vascularity may be indicative of treatment failure.…”
Section: Evolution Of the Vascularity Of The Ectopic Mass Following Mtx Therapymentioning
confidence: 96%
“…Gamzu et al found that upon the administration of MTX, EP is observed to increase in size, which is not associated with a risk for treatment failure, and does not correlate with β-hCG level (16) . A recently published study suggested that the increasing EP size may even be considered a positive sign confirming the effectiveness of MTX therapy (17) .…”
Section: Evolution Of the Size Of The Ectopic Mass Following Mtx Therapymentioning
confidence: 99%